Optimalisasi fungsi Masjid sebagai pusat kegiatan sosial dan keagamaan - Kudus, Ruhul; Irfan, Irfan; Ulum, Fatkhul; Maria, Enung; Jamal, Mardhiana (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
This service aims to optimize the function of the mosque in improving religious education, social activities, and community economic empowerment. The role and function of mosques must be optimized to increase public awareness of the urgency of mosques, in addition to being a center of worship, mosques are also useful as centers of social and economic welfare for the community. The method used was community-based participatory research, involving the congregation of At-taqwa mosque in Gowa. The results showed that mosques that are active in social and economic activities can reduce poverty and increase social solidarity. The programs designed include routine recitation, congregational prayer, teaching reading and writing the Qur'an, and social activities such as gotong royong and aid distribution. Evaluations show increased congregational participation and positive impacts on the spiritual, social, and economic well-being of the community. Optimizing the function of the mosque is very relevant to improve the quality of life of worshipers and the surrounding community.